High‐efficiency green‐yellow light‐emitting diodes grown on sapphire (0001) substrates. Issue 11 (23rd September 2013) - Hashimoto, Rei; Hwang, Jongil; Saito, Shinji; Nunoue, Shinya; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract High‐efficiency green‐yellow InGaN‐based light‐emitting diodes (LEDs) were grown by metal organic chemical vapor deposition on conventional c‐plane sapphire (0001) substrates. The crystal quality of the InGaN quantum well was improved by optimizing the growth temperature and rate. Fabricated LEDs exhibited a high output power of 11.2 mW and external quantum efficiency (EQE) of 25.5% for 560 nm green‐yellow LEDs with an injection direct current of 20 mA. The highest EQE of over 30% was achieved with an injection direct current of 3 mA at an emission wavelength of 568 nm. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)